2011
DOI: 10.1007/s10661-011-1965-2
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the impact of on-site sanitation systems on groundwater pollution in two diverse geological settings—a case study from India

Abstract: On-site sanitation has emerged as a preferred mode of sanitation in cities experiencing rapid urbanization due to the high cost involved in off-site sanitation which requires conventional sewerages. However, this practice has put severe stress on groundwater especially its quality. Under the above backdrop, a study has been undertaken to investigate the impact of on-site sanitation on quality of groundwater sources in two mega cities namely Indore and Kolkata which are situated in two different geological sett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(36 citation statements)
references
References 8 publications
(13 reference statements)
2
32
1
1
Order By: Relevance
“…Concentrations of nitrate in well water near latrines are highly variable. Although a number of studies that detected total or fecal coliforms did not detect elevated nitrate concentrations in wells (Ahmed et al 2002; Dzwairo et al 2006; Howard et al 2002; Padmasiri et al 1992; Still and Nash 2002), other studies have reported nitrate concentrations > 100 mg/L (Banks et al 2002; Girard and Hillaire-Marcel 1997; Lewis et al 1980; Mafa 2003; Pujari et al 2012; Tandia et al 1999). Frequently, groundwater nitrate concentrations near latrines were above local background levels, even if they remained below or near the WHO guideline (Baars 1957; Caldwell and Parr 1937; Chidavaenzi et al 2000; Jacks et al 1999; Zingoni et al 2005).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Concentrations of nitrate in well water near latrines are highly variable. Although a number of studies that detected total or fecal coliforms did not detect elevated nitrate concentrations in wells (Ahmed et al 2002; Dzwairo et al 2006; Howard et al 2002; Padmasiri et al 1992; Still and Nash 2002), other studies have reported nitrate concentrations > 100 mg/L (Banks et al 2002; Girard and Hillaire-Marcel 1997; Lewis et al 1980; Mafa 2003; Pujari et al 2012; Tandia et al 1999). Frequently, groundwater nitrate concentrations near latrines were above local background levels, even if they remained below or near the WHO guideline (Baars 1957; Caldwell and Parr 1937; Chidavaenzi et al 2000; Jacks et al 1999; Zingoni et al 2005).…”
Section: Resultsmentioning
confidence: 98%
“…At a study site in India characterized by a shallow water table and fractured rock aquifer, high concentrations of fecal coliforms were found in domestic wells located near pit latrines and septic tanks (Pujari et al 2012). At a contrasting site, characterized by alluvial formations, the authors detected no or low levels of fecal contamination (Pujari et al 2012).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be an effect of the poor construction of latrines and wells on these farms, which can permit the infiltration of the subsoil by microorganisms, and viruses may thus accumulate on the groundwater resources (Jung et al , 2011; Pujari et al , 2012; Steyer et al , 2011; Wilcock et al , 2011). The concern is that water from artesian wells and springs is often thought to be free of contaminants and the farmers and families living on these locations have been using this as the solely source of drinking water.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors reported that inadequate on-site sanitation design and the hydrogeological conditions of terrain are potential sources of groundwater pollution, including fecal contamination (ARGOSS, 2001;Dzwairo, Hoko, Love, Guzha, 2006;Pujari, Padmakar, Labhasetwar, Mahore, Ganguly, 2011). In Botswana, Staudt (2003) found that eleven out of thirty-one sampled boreholes in the Ramotswa area had nitrate concentrations exceeding the nitrate concentration guideline value of 45 mg/L for drinking water (World Health Organization [WHO], 2006).…”
mentioning
confidence: 99%